2017
DOI: 10.2185/jrm.2940
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of gemcitabine and paclitaxel as third-line chemotherapy in metastatic urothelial carcinoma

Abstract: Background: We evaluated the effectiveness of gemcitabine and paclitaxel therapy in patients with metastatic urothelial carcinoma for whom two lines of sequential chemotherapy had been unsuccessful.Methods: A total number of 105 patients who had previously received first-line chemotherapy consisting of gemcitabine and cisplatin or carboplatin, were treated with second-line gemcitabine and docetaxel therapy between June 2006 and May 2015. Of these patients, 15 with an Eastern Cooperative Oncology Group Performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Recently, mechanisms of acquisition of chemoresistance to gemcitabine in urothelial cancer cells have been outlined. 23 , 24 However, gemcitabine shows a synergistic effect when combined with different chemotherapeutic agents, and several studies have consistently used gemcitabine in sequential therapy, 25 , 26 as in our chemotherapeutic strategies for mUC. As a result, GD therapy after the failure of gemcitabine and platinum-based combination therapy showed good anti-tumor effects: the total ORR waŝ20% and the median OS was 7.6 months for the entire cohort receiving second-line GD therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, mechanisms of acquisition of chemoresistance to gemcitabine in urothelial cancer cells have been outlined. 23 , 24 However, gemcitabine shows a synergistic effect when combined with different chemotherapeutic agents, and several studies have consistently used gemcitabine in sequential therapy, 25 , 26 as in our chemotherapeutic strategies for mUC. As a result, GD therapy after the failure of gemcitabine and platinum-based combination therapy showed good anti-tumor effects: the total ORR waŝ20% and the median OS was 7.6 months for the entire cohort receiving second-line GD therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are few reports on the improvement of QoL with second-line chemotherapy in patients with platinum-resistant UC with a PS of 2 or 3. It has been reported that in patients with platinum-resistant UC, two cycles of combination therapy (gemcitabine 1,000 mg/m 2 on days 1, 8, and 15, and paclitaxel 200 mg/m 2 on day 1 of each 21-day cycle) did not significantly improve scores on all items of the SF-36 (20). However, in that study, this regimen was used in the third-line setting and the study population did not include patients with PS 2 or 3.…”
Section: Relationship Between Overall Survival Periods and Expressimentioning
confidence: 95%